Mapping the Material-Property Space for Feasible Process Operation: Application to Combined Natural-Gas Separation and Storage - Iyer, Shachit S; Hasan, M. M. Faruque (Industrial & engineering chemistry research, 2019)
A multiscale-optimization-based feasibility-mapping approach is introduced to identify the target properties of materials that would guarantee the desired process performance. The approach is successfully applied to screen a database of 178 known and 139 500 hypothetical zeolites to find materials that are most suited for the combined separation and storage (CSS) of natural gas. Maps of material properties that include the equilibrium adsorption loading and the Henry coefficients are obtained for feasible process operation subject to the constraints imposed. On the basis of these maps, materials with high methane-storage capacities but moderate Henry coefficients, such as SBN and h8124791, are found to be most suitable for CSS applications. The constraints imposed on the purity of stored methane and methane loss during the process operation influence the desired material properties. Beyond identifying feasibility, maps of constraint violations are constructed that can be useful in analyzing the effects of material properties on the deviation from feasibility. Ranges of the continuous material-property space are related to the values of total and individual constraint violations, and it is observed that the constraint on loss of methane through the column outlet primarily restricts overall process feasibility for a wide range of material properties. These insights are useful in the systematic design, synthesis, and tuning of new materials for process innovation.